2014
DOI: 10.15181/atee.v1i0.666
|View full text |Cite
|
Sign up to set email alerts
|

Dolphin Assisted Therapy: Innovative Learning for Children With Disabilities

Abstract: In this article the dolphin assisted therapy is presented as an innovative method of learning for children with disabilities. The historical overview of dolphin assisted therapy is introduced. Currently it has received the legal recognition in Lithuania and expanded to family-centered programs. Newly developed dolphin assisted therapy program can be integrated into the education process of the child with disabilities as well as the whole family system. The aim of this article, then, is to focus on the dolphin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A recent study (Rugevičius et al, 2016) evaluating the effectiveness of dolphin assisted therapy for autism spectrum disorder from long-term approach revealed that positive changes in behavior, sensory and cognitive spheres occurred in 60 percent of the children. Kreivinienė & Perttula (2014) conceptualized dolphin assisted therapy as an innovative method for learning where different learning contexts may be applied in support of dolphins.…”
Section: Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study (Rugevičius et al, 2016) evaluating the effectiveness of dolphin assisted therapy for autism spectrum disorder from long-term approach revealed that positive changes in behavior, sensory and cognitive spheres occurred in 60 percent of the children. Kreivinienė & Perttula (2014) conceptualized dolphin assisted therapy as an innovative method for learning where different learning contexts may be applied in support of dolphins.…”
Section: Research Resultsmentioning
confidence: 99%
“…A number of studies including animals in therapeutic activities Davis et al, 2015;Esposito et al, 2011;Kreivinienė, Perttula, 2014;Rugevičius et al, 2016) suggest that human-animal interaction impacts on the welfare of a child and the family in disability situation. Kreivinienė & Vaičekauskaitė (2010) conceptualize that dolphin assisted therapy can be viewed from the systemic perspective, when improvement in dimensions of one family member influences the improvement in inner sense of coherence of all the family system.…”
Section: Discussion About the Resultsmentioning
confidence: 99%